Truncal growth pattern of Yogasana-practising children and adolescents - Debjani Mandal; Uday Sankar Ray; Pratiti Ghosh (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: Truncal growth forms a robust skeletal frame which determines athletic execution. At present, yogasana practice is in high demand. AIM: Thus, the evaluation of effect of yogasana on growth pattern during childhood and adolescence (aged 4-15 years) is required. MATERIALS AND METHODS: A cross-sectional study was conducted on Bengalee children of similar socioeconomic status. Anthropometric measurements, namely height (stature), biacromial breadth, and bicristal breadth were analyzed from 864 yogasana-practitioners (YPs) and 738 untrained control participants (CPs), subgrouped into yogasana-practising boys (YBs), yogasana-practising girls (YGs), control boys (CBs), and control girls (CGs). Unpaired t-test was performed to assess the level of significance between the anthropometric parameters of different groups. Correlation of breadth ratio and stature with biacromial and bicristal breadth was determined by Pearson's correlation coefficient. RESULTS: YP had significantly greater biacromial breadth (P < 0.05) and bicristal breadth (P < 0.05) than CP. The mean biacromial breadth decreased, especially in YG. The shoulder and pelvis size were significantly different between YB and CB but not so among females. Growth in breadth ratio was also strongly correlated with bicristal breadth growth. CONCLUSION: Medium-sized shoulder and pelvis in YB and medium-sized shoulder relative to narrow-sized pelvis in YG nullifies the effect of yogasana training on specific bodily growth of YP. Hence, in contrast with high-demand sports, yogasana practice is not reflected on truncal growth.